Androgen receptor signaling inhibitors: post-chemotherapy, pre-chemotherapy and now in castration-sensitive prostate cancer. Issue 8 (15th July 2021) - Mitsiades, Nicholas; Kaochar, Salma
Abstract : Based on pioneering work by Huggins, Hodges and others, hormonal therapies have been established as an effective approach for advanced prostate cancer (PC) for the past eight decades. However, it quickly became evident that androgen deprivation therapy (ADT) via surgical or medical castration accomplishes inadequate inhibition of the androgen receptor (AR) axis, with clinical resistance inevitably emerging due to adrenal and intratumoral sources of androgens and other mechanisms. Early efforts to augment ADT by adding adrenal-targeting agents (aminoglutethimide, ketoconazole) or AR antagonists (flutamide, bicalutamide, nilutamide, cyproterone) failed to achieve overall survival (OS) benefits, although they did exhibit some evidence of limited clinical activity. More recently, four new androgen receptor signaling inhibitors (ARSIs) successfully entered clinical practice. Specifically, the CYP17 inhibitor abiraterone acetate and the second generation AR antagonists (enzalutamide, apalutamide and darolutamide) achieved OS benefits for PC patients, confirmed the importance of reactivated AR signaling in castration-resistant PC and validated important concepts that had been proposed in the field several decades ago but had remained so far unproven, including adrenal-targeted therapy and combined androgen blockade. The past decade has seen steady advances toward more comprehensive AR axis targeting. Now the question is raised whether we have accomplished the maximum AR axis inhibition possible or there is still room for improvement. This review, marking the 80-year anniversary of ADT and 10-year anniversary of successful ARSIs, examines their current clinical use and discusses future directions, in particular combination regimens, to maximize their efficacy, delay emergence of resistance and improve patient outcomes.